Efek Pupuk KCl dan SP-36 Terhadap Kalium Tersedia, Serapan Kalium dan Hasil Kacang Tanah (Arachis hypogaea L.) pada Tanah Brunizem - Ch. Silahooy (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
Molucca, in general and especially Ambon has ground nut fields with low productivity compared to national yield of ground nut. Brunizem has low levels of K and P nutrients. These conditions were interesting to be investigated. The research took place in a plastic house for two months in Halong village, sub district Baguala. The research was done in a Completely Randomized Design with 2 Factors. The first factor was three levels of K fertilizer, ie K0 (no K fertilizer application), K1 ( 0.5 g KCl/pot) and K2 ( 1.0 g KCl/pot). The second factor was three levels of P fertilizers, ie P0 (no P fertilizer application), P1 (0.6 g SP-36/pot), and P2 (1.2 g SP-36/pot). The aim of the research was to investigate the availability and sorption of potassium, growth and dryweight-of ground nut (Arachis hypogaea L.) seed due to the application of KCl and SP-36 fertilizers on Brunizem. The results of this research showed a high significant effect of potassium fertilizer treatment on soil-pH, availibility and sorption of K, plant height, stem diameter, and dryseed weight of ground nut. Treatment g P fertilizer has a significant effect on soil pH, available K, plant height, and dry weight of seed. The interaction of K and P fertilizers had no significant effect on K availability and sorption of K. K availability of 0.26 me/100 g and 4.95% of plant-K was attained at the treatment of 1.0 g KCl/pot. The high dry yield of ground nut (17.35 g/pot) was achieved at dose of 1.0 g KCl/pot, meanwhile dose of 1.2 g SP-36/pot gave the highest seed-dry yield of ground nut